2020
DOI: 10.1007/s11121-020-01148-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Intervention Mapping to Developmentally Adapt an Online HIV Risk Reduction Program for Adolescent Men Who Have Sex with Men

Abstract: Adolescent men who have sex with men (AMSM) experience a dramatic health disparity in HIV, accounting for over 80% of new diagnoses among youth. Current evidence-based HIV prevention programs, however, focus primarily on adults and heterosexual youth, thereby missing the unique experiences and socio-environmental contexts of AMSM aged 13-18. To address these gaps, we used the Intervention Mapping (IM) protocol to developmentally adapt an existing evidence-based online HIV risk reduction program (i.e., Keep it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Additionally, this paper demonstrates how theory (SEL framework and the Prosocial Behavior model) can be embedded into the IMP process and it highlights how stakeholder consultation and collaboration can bridge the theory and practice divide. Computer-based health behavior interventions for young people have been developed previously using the IMP in healthrelated contexts such as drinking behavior [52], safe sex behavior [53,54], healthy diet and physical activity [55] and cyberbullying [56,57]. However, this is the first study that has demonstrated the application of the IMP process to the design of a digital game specifically elaborated to promote socio-emotional skills and prosocial behaviors in middle childhood as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this paper demonstrates how theory (SEL framework and the Prosocial Behavior model) can be embedded into the IMP process and it highlights how stakeholder consultation and collaboration can bridge the theory and practice divide. Computer-based health behavior interventions for young people have been developed previously using the IMP in healthrelated contexts such as drinking behavior [52], safe sex behavior [53,54], healthy diet and physical activity [55] and cyberbullying [56,57]. However, this is the first study that has demonstrated the application of the IMP process to the design of a digital game specifically elaborated to promote socio-emotional skills and prosocial behaviors in middle childhood as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous computer-based health behavior interventions for young people have been developed using the IMP in health-related contexts such as drinking behavior [52], safe sex behavior [53,54], healthy diet and physical activity [55] and cyberbullying [56,57]. Yet, a digital game specifically designed to promote socio-emotional skills and prosocial behaviors in middle childhood using IMP is missing.…”
Section: Introductionmentioning
confidence: 99%
“…IM guided the planning, development, and evaluation of the fully automated and open-access web-based intervention [ 26 ]. IM has proven effective for the development of many web-based interventions [ 27 , 28 ]. Furthermore, this strategy supports a theory-based approach that focuses on understanding and accommodating the needs and perspectives of the end users at all stages of the design.…”
Section: Methodsmentioning
confidence: 99%